Oxygen incorporation in directional solidification of photovoltaic silicon: Experimental facts and modeling. (December 2021) - Camel, D.; Drevet, B.; Fayard, E.; Eustathopoulos, N.
Abstract: Oxygen, an usual impurity of photovoltaic silicon, is known to be detrimental for the electrical performances of this material. In this investigation, solidification experiments are performed in coated silica crucibles in order to study the influence of crucible size, crucible coating, argon flow and crucible material on silicon contamination by oxygen. In order to interpret the results, an analytical, semi-quantitative model is established taking into account two oxygen flows: the contamination flow at the crucible/silicon interface and the evacuation flow at the silicon free surface. Graphical abstract: Image, graphical abstract